In‐situ assessment of the spatial arrangement of step–pool units on eroded rills. Issue 14 (13th August 2019) - Giménez, Rafael; Zubieta, Elena; Govers, Gerard; Campo‐Bescos, Miguel A.
Abstract: Rills are generated on homogeneous hillslopes by the action of different discharges and evolve morphologically over short timescales due to a strong interaction between the flow and bed morphology. Such an interaction generates a reconfiguration of the bed geometry. Previous works suggest that bed geometry is often characterized by alternation between pools and flat reaches (steps). Each step–pool unit may contribute to hydraulic resistance and affects flow behaviour. The objectives of this work are (i) to assess different (innovative) techniques for the in‐situ assessment of rill bed geometry, (ii) to use these techniques to assess the geometry of eroded rills in situ in order to determine the spatial arrangement in the bed macro‐scale roughness and (iii) finally to analyse the role of slope and discharge as driving factors associated with the development of these macroforms. Roughly rectilinear, long rills were formed in the field as a result of combining different slope and discharges. Photogrammetry provided detailed digital elevation models (DEMs) before and after the experiments. The rills were morphologically characterized from the DEMs. In each rill, the presence of step–pools was identified from long profiles according mainly to morphological criteria published elsewhere, but with ad hoc critical threshold values more appropriate for small eroded channels. The minimum slope required for the development of step–pool units seems to be somewhere between 5 and 15%. Discharge seems to affect pool size or roughness amplitude. There does not seem to be a clear step–pool periodicity. However, external factors could have affected the normal growth and alternation of these structures. Identification of steps and pools from longitudinal elevation profiles can be objectively accomplished using a series of geometric rules originally proposed for rivers and large channels, and adapted to rills. © 2019 John Wiley & Sons, Ltd. Abstract : Reshaping of the rill bed by rill flow is revealed by step‐pool units whose sequences vary with slope and discharge. The rill bed‐hydraulics interaction have a manifest effect on rill hydraulics. Identification of steps and pools in rills from elevation profile can be objectively made using geometric rules proposed for rivers and adapted to rills.